Państwa Grupy Wyszehradzkiej wobec Kaukazu Południowego .......... 85 - Brodowski, Jan (Rewolucja rosyjska. Spuścizna : międzynarodowe echa rewolucji, 2017)
THE ATTITUDE OF VISEGRAD GROUP STATES TOWARDS THE SOUTH CAUCASUSThe breakup of the Soviet Union enabled not only the liberation of Central and Eastern Europe from the yoke of Moscow, but also the independence of Georgia, Armenia and Azerbaijan. The possibility of unimpeded pursuit of alliances led to the establishment of the Visegrad Group (V4) at the beginning of the 1990s on the basis of the common interests and experiences of the governments in Warsaw, Prague, Bratislava and Budapest. Similar challenges posed by aspirations for membership in the European Union and NATO influenced the shape of V4’s foreign policy. However, the attitude of the four European capitals towards the post-Soviet space was based on different premises. The enlargement of the European Union in 2004 with all Visegrad Group countries, and in particular the adoption of the European Neighborhood Policy (ENP), has given them a new framework for cooperation. V4 countries have been given the opportunity to pursue their interests not only at the level of bilateral contacts but also within the new multilateral cooperation formula. Eastern Partnership (EAP) also addressed the South Caucasus republics, became an important element in shaping relations within the ENP. Thus, can it be said that the V4 countries are guided by common interests in their relations with Georgia, Armenia and Azerbaijan? Or can we just isolate common areas of cooperation (presence in the region, energy or development aid), while interests and priorities remain different? The fact that V4 states differ in terms of their potential largely determines their varying abilities to influence the South Caucasian states, which makes it worthwhile to discuss the actions that they may undertake as well as the need to define them.